Pengaruh Gaya Hidup terkait Konsumsi Makanan terhadap Keputusan Pembelian dan Nilai Pelanggan dalam Menggunakan Layanan Pesan Antar Makanan Online pada Generasi Z - Azzahra, Naila; Utami, Hesty Nurul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The development of digital technology has driven significant changes in various aspects of life, including food consumption patterns, particularly among Generation Z. One rapidly growing innovation is Online Food Delivery (OFD) services. Lifestyle changes and technological convenience require culinary business actors to understand consumer segmentation accurately in order to remain competitive. This research was conducted at three universities in the Jatinangor District, namely Padjadjaran University, Bandung Institute of Technology (Jatinangor Campus), and the Indonesian Cooperative University (IKOPIN). The aim is to identify the characteristics of Generation Z users of OFD services. This study adopts a quantitative approach using a survey method, with a sample size of 196 respondents. The results show that the concepts of food-related lifestyle, purchasing decisions, and customer value are perceived positively by respondents, making them relevant in the context of online food delivery usage among Generation Z. This research provides a theoretical contribution by enriching the literature on the Food-Related Lifestyle (FRL) concept in the digital context, as well as a practical contribution for food industry players and OFD service providers in designing marketing strategies that align with the characteristics of Generation Z consumers.